General Participation System as a tool of decentralization and his impact on the management of territorial entities (2016)
It presents a perspective of analysis that explains from the normative part and argumentative all development and impact decentralization and management that have the territorial entities using as a tool the GENERAL PARTICIPATION SYSTEM (GPS), having as finality to make more precise managements depending on each region through of the public professionalization; but it has been overshadowed by embezzlement of these money so it is necessary to criticize and analyze situations that produce lack of management and therefore poor quality results in the economic development of the country. Therefore the results of education, water, utilities and others were analyzed during the year 2013 according to the National Planning Department, and thus leave a constructivist stance.